An empirical investigation of knowledge management, organizational innovation, organizational learning, and organizational culture: Examining a moderated mediation model of social media technologies. Issue 3 (9th December 2020) - Hussain, Iftikhar; Mujtaba, Ghulam; Shaheen, Imrab; Akram, Sabahat; Arshad, Adeel
Abstract : This study investigates the direct impact of knowledge management on organizational innovation and indirect impact through organizational learning and organizational culture, using diffusion of innovation theory. Moreover, these relationships were also empirically tested in the presence of social media technologies as potential moderator. Simple random sampling was used to select 380 respondents from small and medium‐sized enterprises (SMEs) operating in Pakistan. Structural equation modeling (SEM) was employed to measure the fitness of the proposed model via LISREL 8.8. Our results show that knowledge management positively influences organizational learning and organizational culture. Moreover, organizational culture and learning significantly influence organizational innovation. Similarly, knowledge management has a significant indirect impact on organizational innovation through organizational learning and culture. Furthermore, the moderating impact of social media technologies in the relationship between organizational learning and organizational innovation is also found significant. The present study offers novel and interesting insights by indicating that the management of SMEs realizing the importance of knowledge management and inspiring workers to practice organizational learning, organizational culture, and social media technologies can facilitate organizational innovation in SMEs.